(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
The specific purpose of the research was to construct an achievement test in the area of philosophy of education for master level students in universities of Punjab (Bahauddin Zakariya University Multan, The Islamia University of Bahawalpur and University of Sargodha, Sargodha. Test comprises 60 multiple-choice items, selected from the item bank constructed by researcher. This test was administered to 231 male and female students of M.A. Education and M.Ed. selected randomly. Data were analysed through Rasch model. As the result of Rasch calibration, three items were tossed out of the test. Figure latent continuum showing position of items and persons was made. This study suggests that to cover the whole syllabus items should be increased. An effort should be made to take a greater number of samples for the study, so that item analysis through Rasch Model can show its probability.